Chocolate substitution with sweet soy sauce in making steamed brownies - Fathoni, Luthfi Abdulla; Listiaty, Tia (Surya Hijau Manfaat, 2025)
This study aims to find out how sensory Assessment and receipt of steamed brownies with the substitution of sweet soy sauce differ and how the cost of production differs. The background of this study is that it looks at the opportunity for the presence of sweet soy sauce to be abundant in the market, as well as the opportunity for the absence of steamed brownie products that use sweet soy sauce. The Number of participants in this study amounted to 15 lecturers and students from The International Prima Tourism Polytechnic. The sampling technique is based on Gay and Diehl's theory (1992), which states that in experimental research, at least 15 people are trained panelists who are lecturers who are experts in their fields and students who practice real work in pastry. The hedonic test was conducted on 30 untrained panelists. Data collection is done using questionnaires/questionnaires with an ordinal scale. The analytical methods used are descriptive sensory test analysis and hedonic test. Data analysis techniques group random design analysis techniques and variant analysis (ANOVA) using calculations through Microsoft Excel were used. The study's results based on sensory and hedonic tests showed that steamed brownie products coded B2K2 with an increase in the concentration of sweet soy sauce by 30% is the best formulation based on Color, taste, aroma, Texture, and appearance parameters. It also showed that the cost of producing steamed brownies that use sweet soy sauce was lower than that of steamed brownies control products.